2011
DOI: 10.2106/jbjs.j.00347
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gait Following the Scandinavian Total Ankle Replacement

Abstract: This study demonstrated that, at the time of intermediate-term follow-up and in comparison with the effects of ankle arthrodesis on gait as reported in previous studies, total ankle arthroplasty was associated with a more normal ankle function and a more normal gait, both kinetically and in terms of temporal-spatial parameters. More importantly, the study demonstrated marked improvement in multiple, objective parameters of gait following total ankle arthroplasty as compared with the patient's own preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 29 publications
5
101
0
Order By: Relevance
“…(1) to understand the biomechanical properties of human gait (eg, characteristics of normal and/or pathological gait), 18,41,82 (2) to analyze the components of human gait (eg, study the biomechanical components of the foot and their relationship to one another during gait 45 ), and (3) to make clinically meaningful inferences regarding the anatomic and biomechanical function (eg, to objectively measure the effect of treatment 6,11,68 ).…”
Section: What Is Gait Analysis?mentioning
confidence: 99%
“…(1) to understand the biomechanical properties of human gait (eg, characteristics of normal and/or pathological gait), 18,41,82 (2) to analyze the components of human gait (eg, study the biomechanical components of the foot and their relationship to one another during gait 45 ), and (3) to make clinically meaningful inferences regarding the anatomic and biomechanical function (eg, to objectively measure the effect of treatment 6,11,68 ).…”
Section: What Is Gait Analysis?mentioning
confidence: 99%
“…Furthermore, premature deterioration of other foot joints with substantial arthritic changes was found in the foot as a long-term result [4]. On the other hand, significant improvements including subjective outcome, more normal ankle function, gait kinematics and gait kinetics were observed following total ankle replacement (TAR) [5,6]. In cadaveric studies it was suggested that modern prosthetic designs are even able to achieve close to normal kinematics [7].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable dorsal/plantar flexion data are reported for gait analysis of patients provided with other TAR designs [80][81][82]. A considerably higher flexion was assumed for displacement-controlled wear testing.…”
Section: Wear Testmentioning
confidence: 99%